n Morfologiese ondersoek van Tylosema esculentum (Burch.) Schreiber en Tylosema fassoglense (Schweinf.) Torre en Hillc. in Suidelike Afrika - Robbertse, P.J. (Petrus Johannes), 1932- (University of Pretoria, 2022)
Thesis (DSc)--University of Pretoria, 1982.